Pengaruh Penerapan Model Pembelajaran Eliciting Activities untuk Meningkatkan Hasi Belajar Matematika Siswa Kelas VIII-B SMP Bajiminasa - Puspita Ayu, Novalinda; Amin Noor, Chadid (Jurnal Teknologi dan Bisnis Cerdas, 2025)
This study is classroom action research, which addresses actual problems encountered by teachers in the field. The purpose of this research is to identify and analyze the implementation of th Eliciting Activities learning model among Grade VIII-B students of SMP Bajiminasa. The subjects of this study were 17 students from Class VIII-B of SMP Bajiminasa in the 2023/2024 academic year. The research data were obtained from learning outcome tests and observations conducted during Cycle I and Cycle II. The results showed that: 1)  Students’ mathematics learning outcomes in Cycle I were in the medium category, with an average score of 64.44, a standard deviation of 11.108, and a median of 64, which did not yet meet the minimum mastery criterion (KKM) of 75; 2) In Cycle II, students’ mathematics learning outcomes were in the high category, with an average score of 80.65, a standard deviation of 10.974, and a median of 82, which had met the minimum mastery criterion, with 85% of students scoring above 70 out of an ideal score of 100. The implementation of the Eliciting Activities learning model can improve the mathematics learning outcomes of Grade VIII-B students at SMP Bajiminasa.